2014
DOI: 10.1055/s-0034-1376197
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Outcome of Patients with Skull Base Chordoma: A Meta-analysis

Abstract: Objective Chordoma is a locally aggressive tumor. The aim of this study was to assess the efficacy of different surgical approaches and adjuvant radiation modalities used to treat these patients. Design Meta-analysis. Main Outcome Measures Overall survival (OS), disease-specific survival (DSS), and progression-free survival (PFS). Results The 5-year OS and PFS rates of the whole cohort (n = 467) were 86% and 65.7%, respectively. The 5-year DSS for patients who underwent open surgery and endoscopic surgery was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…However, with continuous expansion of its applications, the disadvantages of endoscopic endonasal skull base surgery have become apparent, such as its two-dimensional view, long and narrow corridor, difficult hemostasis, high cerebrospinal fluid leakage rate, and serious damage of nasal structure [5][6][7][8]. Many reports have compared, summarized, and reflected on the advantages and disadvantages of endoscopy and microscopy in treatment of skull base lesions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. To facilitate scientific decision-making regarding different technical means to manage skull base disease and improve surgical quality, we have herein summarized our 10-year experience of endoscopic endonasal skull base surgery with an emphasis on its advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…However, with continuous expansion of its applications, the disadvantages of endoscopic endonasal skull base surgery have become apparent, such as its two-dimensional view, long and narrow corridor, difficult hemostasis, high cerebrospinal fluid leakage rate, and serious damage of nasal structure [5][6][7][8]. Many reports have compared, summarized, and reflected on the advantages and disadvantages of endoscopy and microscopy in treatment of skull base lesions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. To facilitate scientific decision-making regarding different technical means to manage skull base disease and improve surgical quality, we have herein summarized our 10-year experience of endoscopic endonasal skull base surgery with an emphasis on its advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have shown improved rates of progression-free survival with GTR. [ 3 14 68 86 ] Improved rates of progression-free survival with adjuvant radiotherapy has also been demonstrated,[ 16 22 89 ] however, a superior rate of progression-free survival with GTR and adjuvant radiation compared with subtotal resection and adjuvant radiation[ 3 ] have maintained GTR, when safely possible, as the primary mode of treatment. Surgical management via lateral and midline microsurgical approaches have been described.…”
Section: Indications and Outcomes Of The Fully Endonasal Endoscopic Amentioning
confidence: 99%
“…completed a meta-analysis to assess the efficacy of different surgical approaches for patients harboring chordomas. [ 3 ] The analysis identified 467 patients from 28 published studies and complete individual data was available for compiled data analysis for 165 cases. For open (transcranial) surgery versus endoscopic surgery, no significant difference was found in the 5-year disease specific survival rate (45% vs. 49%, P = 0.07), and the progression-free survival rate (94% vs. 79%, P = 0.11).…”
Section: Indications and Outcomes Of The Fully Endonasal Endoscopic Amentioning
confidence: 99%
“…Because surgery of the skull base or sacral area is difficult due to the complex anatomy and adjacent critical structures, complete tumor resection is often impossible, and patients usually receive adjuvant therapy or radiotherapy like proton therapy 4. Thus, the benefit of adjuvant treatment according to the tumor location has been investigated 567. Meanwhile, few studies have conducted a detailed comparison of the histologic features of skull base and spinal/sacral chordomas.…”
Section: Introductionmentioning
confidence: 99%